Navigating the Crosscurrents: Canadian Colleges and Universities in an Era of Federal Policy Shifts and Fiscal Constraints - Al-Haque, Rashed; Legusov, Oleg; Knight-Grofe, Janine; Charles, Anne; Davis, Alan (Canadian Journal of Higher Education / Revue canadienne d'enseignement supérieur)

(untitled) (Canadian Society for the Study of Higher Education, 2026)
The Canadian college sector is facing a systemic crisis driven by the perfect storm of chronic provincial underfunding and abrupt federal immigration policy shifts. This moderated discussion explores how reforms to Canada’s immigration laws with respect to international students have triggered a crisis for Canadian postsecondary institutions, including substantial budget losses, program cancellations, and significant human costs for international students and college and university employees. Through professional perspectives from advising, department leadership, faculty, and executive, the authors detail institutional responses to fiscal constraints and operational uncertainty. Using case studies from Seneca Polytechnic, Durham College, and Conestoga College in Ontario, and Kwantlen Polytechnic University in British Columbia, the moderated discussion highlights the precarious reliance on international tuition and the resulting erosion of campus community. Ultimately, the authors argue that this crisis necessitates a new social contract for Canadian higher education, urging a fundamental transformation of funding models and a renewed focus on institutional integrity and public purpose.